Total Synthesis of Natural Products using Gold Catalysis. Issue 24 (2nd November 2022) - De, Soumik; Dan, Aritra Kumar; Sahu, Raghaba; Parida, Sagarika; Das, Debadutta
Abstract: Gold catalysis is an extremely enthusiastic field of investigation in the catalysis area. The development of alternative, highly inventive, precompetitive techniques based on gold catalysis has paved the way for executing a broad spectrum of chemical transformations from uncomplicated starting materials. The total synthesis of natural products is a complex and more complicated task. An amalgamation of natural product synthesis through gold‐catalysis has been a thought‐provoking job. The protocol has solved several problems related to the synthesis of numerous complicated natural products. Thus, this review has outlined some of the most notable benchmarks from the last seven years (2015–2021) on gold catalysis and their application in the total synthesis of numerous natural products. The strategy acquired by the authors to accomplish the total synthesis will be elaborately discussed by emphasizing the role of the gold‐catalyzed reactions. Abstract : The total synthesis of natural products is a complex and more complicated task. An amalgamation of natural product synthesis through Gold‐catalysis has been a thought‐provoking job. This review has outlined some of the most notable benchmarks from the last six years (2016–2021) on the role of Gold catalysis and their application in the total synthesis of numerous natural products.